Chromosomal and genomic organization of Ty1-copia-like retrotransposon sequences in the genus Avena - Katsiotis, Andreas; Schmidt, T.; Heslop-Harrison, J. S. (My University, 1996)
A cloned repetitive sequence, pAvKB30, obtained from an Avena vaviloviana (AB genome) genomic library, along with two polymerase chain reaction products derived from the conserved region of the reverse transcriptase (RT) gene of retrotransposons, were characterized molecularly and cytologically. The cloned DNA fragment was a dispersed repeat present in all Avena species used in this study (A. strigosa, A. clauda, A. vaviloviana, A. magna, and A. sativa). The fragment was sequenced (210 bp) and found to be 69.5% homologous to part of WIS-2-1 A, and 60.5% homologous to the leader sequence of BARE-1; both of these elements have been characterized as Tyl-copia-like retrotransposons in wheat and barley, respectively. In situ hybridization of pAvKB30 to diploid, tetraploid, and hexaploid oat species revealed that the probe is present on both arms of all chromosomes (A, B, C, and D genomes) but is excluded from their centromeric and nucleolar organizer regions. By using double in situ hybridization in hexaploid A. sativa (ACD genome), pAvKB30 was found to be present in lower copy numbers in C-genome chromosomes compared with A- and D-genome chromosomes. Furthermore, under low stringency conditions, pAvKB30 hybridized on Southern blots containing barley, wheat, rye, and Arrhenatherum DNA. However, under high stringency conditions, it hybridized only OB Arrhenatherum DNA, which is considered to be the genus most closely related to Avena. All Avena species included in this study yielded a PCR product when the primers from the RT domain of retrotransposons were used. Two products, rtA, obtained by using A. strigosa (A s genome) as template, and rtC, obtained by using A. clauda (C p genome) as template, gave Southern and in situ hybridization results similar to pAvKB30, but each was more abundant in its genome of origin.
Keywords: Genomes; In situ hybridization; Oats; Repetitive sequence; Translocations